A fibril-scale visco-hyperelastic model for the mechanics of vocal-fold tissues - Terzolo, Alberto; Bailly, Lucie; Orgéas, Laurent (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionModeling the mechanics of human vocal folds during phonation is a challenging task. This is partly due to the mechanics of their soft and highly anisotropic fibrous tissues, which undergoes finite strains with both elasticity and strain-rate sensitivity.MethodsWe propose a visco-hyperelastic micro-mechanical model capable of predicting the complex cyclic response of the vocal-fold fibrous tissues based on their histo-mechanical properties. For that purpose, we start from the hyperelastic micro-mechanical model proposed by Terzolo et al., J. Mech. Behav. Biomed. Mater. 128:105118 (2022). We include in the model non-linear viscoelastic contributions at the fibril scale to account for the dissipative and time-dependent response of vocal-fold tissues.Results and DiscussionThe relevance of the model is demonstrated and discussed through comparison with a comprehensive set of reference experimental data, within a wide range of loading modes, strains, and strain rates: cyclic and multi-axial loadings at finite strains (tension, compression and shear), along with small-amplitude oscillatory shear (SAOS) and large-amplitude oscillatory shear (LAOS) from low to high frequencies. This study elucidates how the viscoelasticity of vocal-fold tissues can result from combined time-dependent micro-mechanisms, such as the kinematics and the deformation of their fibril bundles, along with the mechanical interactions likely to develop among fibrils and the surrounding amorphous matrix.